The Implementation of Stunting Prevention Program during COVID-19 Pandemic in Pandeglang Regency - Shinta Novelia; Rosmawati Lubis; Linda Yuliani; Hadrian Marta (Nursing and Health Sciences Journal (NHSJ), 2021)
Background: The nutritional status of pregnant women greatly affects the health and development of the fetus. Impaired growth in the womb can cause low birth weight, which triggers stunting. Stunting is a condition of toddlers who have short body size and are not suitable for age caused by malnutrition from both mother and child. Objective: to determine the implementation of stunting prevention programs during the Covid- 19 pandemic at the work area of the Banjar Health Center, Pandeglang Regency in 2021. Methodology: The study used in this study was an analytic observational study with a cross sectional approach. The sample in this study was 100 respondents using SPSS with a frequency distribution table using univariate analysis. Results: The research variable for the class of pregnant women obtained a value of 72.0%, for giving Biscuits additional foods a value of 93.0% and for counseling of ranting kelor obtained a value of 81.0%. Conclusions and Recommendations: Prevention of stunting after the Covid-19 pandemic greatly affects the program activities carried out by the Banjar Health Center. It is hoped that this research can provide information, especially to pregnant women and the public, about the importance of preventing stunting since pregnancy.